ANALISIS NILAI KEHIDUPAN PADA NOVEL KADO TERBAIK KARYA J.S. KHAIREN DAN RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SMA (TINJAUAN SOSIOLOGI SASTRA) - Anggie Novita; Rina Hayati Maulidiah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this study is to determine the values ​​of life in the Best Gift Novel, written by J.S. Khairen and Its Relevance to Literature Learning in High Schools through the study of the sociology of literature. The object of this study is the Best Gift Novel by J.S. Second printing of Khairen, July 2022. The method used iis descriptive qualitative. The data in this study are taken from the  text, contained in the Best Gift Novel by J.S. Khairen. Data are analyzed by reading and note-taking techniques. The results of this study show the values ​​of life in the Best Gift Novel by J.S. Khairen includes social values ​​which include helping each other, friendship, cooperation, caring for others. Moral values ​​that include never giving up, honesty, responsibility, compassion. Religious values ​​that include prayer, gratitude, gratitude, sincere. The study of these values ​​can be integrated into everyday life which can shape the character of students, in case of that the Best Gift Novel by J.S. Khairen can be relevant to Literature Learning in High Schools.